The relation between new technologies and power in Greece: perceptions of people in positions of power - Kondyli, Dimitra (The Greek Review of Social Research, 2015)
The objective of this paper is to delve into the question of whether and how the Information and Communication Technologies (ICTs) are channels through which many forms of power are being exercised. The analysis will be based on the findings drawn from interviews with persons having been appointed in powerful positions in the Greek public administration and under this role have contributed to the ICTs usage as well as, secondary written sources on public administration. The main elements of this analysis include an examination of a. the nature of power, b. the subjects in positions of power within public administration as are defined within the framework of this paper, c. the ideologies of modernisation and globalisation as vehicles to the changes incurred regarding the ICTs, and finally d. the transmission of the aforementioned to wider society.